2017
DOI: 10.1039/c6pp00407e
|View full text |Cite
|
Sign up to set email alerts
|

ASTHMA — comparing the impact of vitamin D versus UVR on clinical and immune parameters

Abstract: The incidence of asthma has increased markedly since the 1960s and is currently estimated to affect more than 300 million individuals worldwide. A number of environmental factors are implicated in asthma pathogenesis, one of which is vitamin D. Vitamin D deficiency is a global health concern and has increased in parallel with asthma incidence. Epidemiological studies report associations between low vitamin D status, assessed as circulating levels of 25-hydroxyvitamin D, with asthma incidence, severity, exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…Vitamin D insufficiency / deficiency are extremely common in the developed world [64] and a healthy diet alone rarely contains adequate vitamin D to achieve sufficient status. Although ultraviolet (UV) light supplementation might be an option [65], population-level oral vitamin D supplementation may be necessary to alleviate the epidemic of vitamin D deficiency and reduce harm from air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D insufficiency / deficiency are extremely common in the developed world [64] and a healthy diet alone rarely contains adequate vitamin D to achieve sufficient status. Although ultraviolet (UV) light supplementation might be an option [65], population-level oral vitamin D supplementation may be necessary to alleviate the epidemic of vitamin D deficiency and reduce harm from air pollution.…”
Section: Discussionmentioning
confidence: 99%
“… 44 In addition, vitamin D deficiency may contribute to asthma severity. 45 An increase in serum vitamin D levels was observed in 73 patients with ankylosing spondylitis who stayed at moderate altitude for 3 weeks during spring. 46 It is possible that increased UVR exposure at moderate altitude may improve serum vitamin D levels in asthmatic patients, but this should be tested in future, well‐controlled, studies.…”
Section: Uv Radiation At Moderate Altitudementioning
confidence: 96%
“…Morgan et al [ 41 ] noted that asthma incidence has increased in parallel with temporal increases in vitamin D deficiency, that epidemiological studies have reported associations between low serum 25(OH)D and increased asthma incidence, and that some evidence exists for a positive correlation between asthma incidence and latitude. Hollams et al [ 42 ] reported that serum 25(OH)D <50 nmol/L in childhood was positively associated with increased risk for asthma or wheeze in a small longitudinal study of 263 children (198 participated up to age five, and 147 up to age 10).…”
Section: Evidence For Health Benefits Of Sun Exposurementioning
confidence: 99%
“…However, this benefit was independent of starting 25(OH)D levels. Mechanistically, vitamin D may not only regulate immune cell activity to reduce infections and sensitization but may also regulate the development of structural cells of the lung [ 41 ]. Some trials have also reported reduced development of wheeze or asthma, but not respiratory tract infections, in offspring of pregnant women supplemented with vitamin D; this effect was independent of starting 25(OH)D levels.…”
Section: Evidence For Health Benefits Of Sun Exposurementioning
confidence: 99%